2017
DOI: 10.21831/elinvo.v2i1.16633
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Implementation of an Educational Multimedia Interactive Operation System Using Lectora Inspire

Abstract: The objective this research to produce a valid interactive learning tool and practice based on learning media Lectora Inspire; knowing the student response against the learning tool, and knowing the student learning outcomes after using Lectora inspire learning media. Research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 1 publication
1
32
0
6
Order By: Relevance
“…(2-tailed) 0.041 <0.05 and -t count (-2.092) <-t table (-2.001) then based on the criteria H0 is rejected and Ha is accepted, so there is a difference in the improvement of students' conceptual skills on special topic of acids and bases using Lectora Inspire's computer media taught with power point media. Increased of the conceptual skills of N-gain students using this lectora inspire media is also supported by research presented by Wibawa [12], the average percentage of responses to student learning achievement is 84.375%. Based on this data it can be concluded that the media lectora obtain good results and it can be effective as a learning tool to support the students' learning activities.…”
Section: Discussionsupporting
confidence: 58%
“…(2-tailed) 0.041 <0.05 and -t count (-2.092) <-t table (-2.001) then based on the criteria H0 is rejected and Ha is accepted, so there is a difference in the improvement of students' conceptual skills on special topic of acids and bases using Lectora Inspire's computer media taught with power point media. Increased of the conceptual skills of N-gain students using this lectora inspire media is also supported by research presented by Wibawa [12], the average percentage of responses to student learning achievement is 84.375%. Based on this data it can be concluded that the media lectora obtain good results and it can be effective as a learning tool to support the students' learning activities.…”
Section: Discussionsupporting
confidence: 58%
“…Dalam Raharjo (2012) menyebutkan beberapa prinsip pemilihan media yakni : (a) kejelasan maksud dan tujuan dalam pemilihian media; (b) familiaritas media, yang melibatkan pengetahuan akan sifat ciri-ciri media yang akan dipilih, dan (c) sejumlah media dapat diperbandingkan karena adanya beberapa pilihan yang kiramya lebih sesuai dengan tujuan pengajaran Inovasi sangat mudah dalam menciptakan media pembelajaran yang sesuai dengan karakter siswa dalam era modern. Sependapat dengan Wibawa (2017) bahwa inovasi dalam mengambangkan kreatifitas dalam menggunakan media sebagai pendukung pembelajaran. Adapun contoh media pembelajaran yang berinovasi sudah mengalami inovasi yaitu multimedia interaktif.…”
Section: Pendahuluanunclassified
“…Berikut ini merupakan hasil penelitian dan pengembangan media pembelajaran yang telah dilakukan berdasarkan tahap pengembangan dengan menggunakan model ADDIE. Model ADDIE merupakan salah satu model desain pembelajaran yang sistematis (Wibawa, Harimurti, Anistyasari, & Sumbawati, 2017). Selain itu, model ADDIE merupakan model desain instruksional yang sistematis yang mewakili pedoman yang dinamis dan fleksibel untuk membangun perangkat pengajaran dan pembelajaran yang berkualitas (Moradmand, Datta, & Oakley, 2014).…”
Section: Hasil Dan Pembahasanunclassified